Choosing the optimal HPV vaccine: The health impact and economic value of the nonavalent and bivalent HPV vaccines in 48 Gavi‐eligible countries. Issue 4 (11th August 2020) - Burger, Emily A.; Portnoy, Allison; Campos, Nicole G.; Sy, Stephen; Regan, Catherine; Kim, Jane J.
Abstract: The human papillomavirus (HPV) vaccines may provide some level of cross‐protection against high‐risk HPV genotypes not directly targeted by the vaccines. We evaluated the long‐term health and economic impacts of routine HPV vaccination using either the nonavalent HPV vaccine or the bivalent HPV vaccine in the context of 48 Gavi‐eligible countries. We used a multi‐modeling approach to compare the bivalent with or without cross‐protection and the nonavalent HPV vaccine. The optimal, that is, most cost‐effective, vaccine was the vaccine with an incremental cost‐effectiveness ratio below the per‐capita gross domestic product (GDP) for each country. By 2100 and assuming 70% HPV vaccination coverage, a bivalent vaccine without cross‐protection, a bivalent vaccine with favorable cross‐protection and the nonavalent vaccine were projected to avert 14.9, 17.2 and 18.5 million cumulative cases of cervical cancer across all 48 Gavi‐eligible countries, respectively. The relative value of the bivalent vaccine compared to the nonavalent vaccine increased assuming a bivalent vaccine conferred high cross‐protection. For example, assuming a cost‐effectiveness threshold of per‐capita GDP, the nonavalent vaccine was optimal in 83% (n = 40) of countries if the bivalent vaccine did not confer cross‐protection; however, the proportion of countries decreased to 63% (n = 30) if the bivalent vaccine conferred high cross‐protection. For lower cost‐effectiveness thresholds, the bivalent vaccine was optimal in a greater proportion of countries, under both cross‐protection assumptions. Although the nonavalent vaccine is projected to avert more cases of cervical cancer, the bivalent vaccine with favorable cross‐protection can prevent a considerable number of cases and would be considered a high‐value vaccine for many Gavi‐eligible countries. Abstract : What's new? The nonavalent human papillomavirus (HPV) vaccine has generally been considered to confer enough additional benefit to warrant a higher price. However, most previous analyses did not fully consider possible cross‐protection by the bivalent vaccine and focused on high‐income countries. This study projected the health and economic tradeoffs of using either vaccine in low‐ and middle‐income countries, incorporating recent data on bivalent cross‐protection and Gavi‐negotiated vaccine prices. Although the nonavalent HPV vaccine was projected to avert more cases of cervical cancer, the bivalent vaccine, with an assumed high and long‐lasting cross‐protective efficacy, would be cost‐effective for nearly half of Gavi‐eligible countries.